Mining Disasters Caused and Controlled by Mankind: The Case for Coal Mining and Other Minerals - Part 1: Causes of Mining Disasters - R. V. Ramani (The National Institute for Occupational Safety and Health (NIOSH), 1996)
"In Part 1 of this two-part paper the characteristics of mine disasters and their effects are presented with case studies from coal, metal and non-metal mines leading to an amplification of their causes and opportunities for control. The disasters discussed encompass those which threaten the health and the safety of miners and those which affect the general population. In Part 2 of the paper, which will be published in the November 1995 issue of Natural Resources Forum, the approaches to hazard and disaster control are reviewed with particular attention to laws and regulations to promote health and safety at the workplace, and general welfare in mining communities. Further, a systems approach to disaster control is outlined.The mining industry is one of the three basic industries the other two being agriculture, and wildlife and fisheries. It is the process of mining which makes available the riches of the earth - the energy and mineral resources - to benefit humanity. In fact the progress of the human race through the ages is indelibly attached to prowess in exploiting these riches. The stone, iron and bronze ages are markers not just of a time in history but achievements of monumental proportions in the mining and beneficiation of natural resources. Even in agriculture, the remarkable success stories are associated with the prudent use of mined products to enhance production and productivity. The significance of a thriving mining industry to the wealth and security of a nation is therefore unquestioned.Unfortunately, the public's image of the mining industry is often associated with the mining disasters which receive wide coverage in the local and national media. Mine disasters command tremendous attention because of their infrequent occurrence and the extent of human suffering involved. Whether it is an explosion or a fire, or the opening or closing of a mine, the lives of people are touched by the personal and societal impacts of these events.Courts of inquiry of mining disasters have often concluded that the disaster situation was ever present and could have been detected with diligent search. In addition human error has been identified as one of the most frequent immediate causes for the precipitation of the disaster. For the most part, then, mining disasters are caused by man."